Detection of the Epstein-Barr virus in blood and bone marrow mononuclear cells of patients with aggressive B-cell non Hodgkin's lymphoma is not associated with prognosis - Marques, Herlander (2012)
The Epstein-Barr virus (EBV) is associated with a large spectrum of lymphoproliferative diseases. Traditional methods of EBV detection include the immunohistochemical identification of viral proteins and DNA probes to the viral genome in tumoral tissue. The present study explored the detection of the EBV genome, using the BALF5 gene, in the bone marrow or blood mononuclear cells of patients with diffuse large B-cell lymphomas (DLBCL) and related its presence to the clinical variables and risk factors. The results show that EBV detection in 21.5% of patients is not associated with age, gender, staging, B symptoms, international prog¬nostic index scores or any analytical parameters, including lactate dehydrogenase (LDH) or β-2 microglobulin (B2M). The majority of patients were treated with R-CHOP like (rituximab, cyclophosphamide, doxorubicin, vincristine and prednisolone or an equivalent combination) and some with CHOP-like chemotherapy. Response rates [complete response (CR) + partial response (PR)] were not significantly different between EBV-negative and -positive cases, with 93.2 and 88.9%, respectively. The survival rate was also similar in the two groups, with 5-year overall survival (OS) rates of 64.3 and 76.7%, respectively. However, when analyzing the treatment groups separately there was a trend in EBV-positive patients for a worse prognosis in patients treated with CHOP-like regimens that was not identified in patients treated with R-CHOP-like regimens. We conclude that EBV detection in the bone marrow and blood mononuclear cells of DLBC patients has the same frequency of EBV detection on tumoral lymphoma tissue but is not associated with the risk factors, response rate and survival in patients treated mainly with immunochemotherapy plus rituximab. These results also suggest that the addition of rituximab to chemotherapy improves the prognosis associated with EBV detection in DLBCL.